Factors influencing spinal anesthesia-to-delivery interval in elective cesarean sections: A retrospective analysis - Kinoshita, Michiko; Sakai, Yoko; Nakaji, Yoshimi; Takahashi, Rikako; Matsumoto, Yako; Tanaka, Katsuya (Medicine (Baltimore), 2025)
Previous research has shown that longer intervals from spinal anesthesia (SA) to cesarean delivery are associated with lower umbilical arterial pH levels. This study aimed to identify specific risk factors related to SA-to-delivery interval in elective cesarean sections. In this retrospective analysis, 404 singleton parturients who underwent elective cesarean sections with SA after 37 weeks of gestation were assessed. Factors influencing the SA-to-delivery interval were explored. The correlation between SA-to-delivery interval and umbilical arterial pH levels was also investigated in our cohort. Factors that significantly prolonged the SA-to-delivery interval included higher body mass index (BMI; regression coefficient [RC]: 0.206, P = .003), history of previous cesarean section (RC: 1.699, P = .012), placenta previa/low-lying placenta (RC: 6.141, P < .001), and local anesthetic administration into the epidural space following SA (RC: 3.279, P < .001). The SA-to-delivery interval was slightly yet significantly inversely correlated with umbilical arterial pH (r = -0.163, P = .001). A general linear model, adjusted for age, BMI, predominant ephedrine use, lowest systolic blood pressure between SA and delivery, diabetes mellitus, and hypertensive disorder of pregnancy have established the significant relationship between the SA-to-delivery interval and umbilical arterial pH (RC: -0.0012, P < .001). In conclusion, factors such as higher BMI, previous cesarean sections, placenta previa/low-lying placenta, and local anesthetic administration into the epidural space after SA significantly contributed to extended SA-to-delivery intervals. The SA-to-delivery interval was inversely correlated with umbilical arterial pH.